A Puna Collection of Senecio punae, Main Source of a Versatile Eremophilane-type Ketone - Rodriguez, Ana María del Valle (2016)
Senecio punae Cabrera (Asteraceae–Senecioneae) is an endemic species from Puna semi-desert region of Argentina.The major compound, 4,5-eremophil7(11)9-dien-8-one, also known as dehydrofukinone (D), was isolated from the diethyl ether extract (E) of the plant. The phytochemical constituents from S. punae are presented here for the first time, as well as bioassays employing D, a molecule with versatility to carry out many different biological activities. E and D showed acute molluscicidal activity against the bilharzia vector snail Biomphalaria peregrina with LD50 values of 68.6 and 16.7 µg/mL, respectively. D exerted moderate and strong effects against promastigotes of Leishmania amazonensis and L. braziliensis, with IC50 values of 34.3±1.2 and 9.93±0.17 µg/mL, respectively. Antibacterial effects were also found. Diethyl ether extract (E) and dehydrofukinone (D) were slightly active against Pseudomonas aeruginosa and Staphylococcus aureus at 50 and 25 µg/mL, respectively. However, D and E improved the effectiveness of oxacillin at 6 µg/mL against S. aureus growth and its biofilm, but did not affect beneficial lactobacilli strains. Synergistic effects were also measured between D (23 µg/mL) and ciprofloxacin (0.25 µg/mL) against two P. aeruginosa strains (FIC index = 0.38), as well as against two S. aureus strains (FIC indexes = 0.38 and 0.25). Finally, when 250 µg of either dehydrofukinone (D) or diethyl ether extract (E) were incorporated into the diet of the pest Oryzaephillus surinamensis, an alteration in the feeding behavior of the insect (Repellency indexes = +60 and +10, respectively) was observed.